Synchronously detected seminoma of both testis in a middle aged male with bilateral cryptorchidism - Afsar, Nabila; Wase, Abdul; Fatima, S. Nikhath; Abid, Zakia (International Journal of Scientific Reports, 2016)
Bilateral testicular tumours are rare and 80% occur metachronously. Synchronous bilateral testicular tumours are rare, and bilateral synchronous testicular tumours in bilateral cryptorchidism are extremely rare with only few cases reported previously. A 36 year old male patient presented to surgical OP with complaints of pain in scrotal region of both sides since 6-8 months. He was asymptomatic previously except for complaints of empty scrotal sac. Magnetic resonance imaging performed 6 months back revealed bilateral large oval to mildly irregular inguinal swellings with iso to hyperintense areas measuring 36×23×20 mm on right side and 34×26×20 mm on left side and patient was diagnosed with bilateral undescended testis. Bilateral orchidectomy was performed and the resected specimen was subjected to histopathologic examination. Gross visual examination of the bilateral orchidectomy specimen revealed the larger specimen to measure 7×4×1 cm with grey coloured external surface. Cut section revealed testis measuring 3.5×2 cm and surrounded with fibro adipose tissue. The testicle shows grey brown and grey white areas surrounding a central yellow nodule measuring 1×0.8 cm. The other mass had a yellowish nodular external surface and measured 5.5×4×1 cm. On cut section, normal testicular tissue could not be identified and the entire testis appeared to be replaced by a solid yellowish white homogenous tumour. Sections from the yellowish smaller mass revealed tumour composed of sheets and trabeculae of large polygonal cells with large vesicular nuclei with prominent nucleoli and abundant clear to vacuolated cytoplasm. Focal collections of histiocytes and occasional multinucleated giant cells were also seen. Sections from the other larger mass showed a thick fibrotic tunica albuginea with sclerosed and hypoplastic seminiferous tubules in areas of dense hyaline fibrosis. In the centre, a well circumscribed tumour was seen showing similar histologic features as in the contralateral mass. Epididymis did not show tumour infiltration.